Modality metaphysics, logic, and epistemology - Hale, Bob, 1945-; Hoffmann, Aviv. (Oxford : Oxford University Press, 2010)
The philosophy of modality investigates necessity and possibility, and related notions - are they objective features of mind-independent reality? This volume presents new work on modality by established leaders in the field and by up-and-coming philosophers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Modality (Logic)